The lemmas and inflections of Old English L-nouns - Martín de las Pueblas Yanguas, Laura; Ojangruen López, Ana Elvira (Studia Anglica Posnaniensia, 2023)
The aim of this work is to lemmatise the inflectional forms of the Old English nouns beginning with the letter L. This aim entails the classification of inflectional forms by declension type. The sources of the study comprise dictionaries and corpora of Old English, including the York corpora as well as ParCorOEv2. An open access annotated parallel corpus Old English-English. The methodology relies on database software, used for gathering and classifying information, which is structured, standardised, and made available for searches and information retrieval. The data include 1,657 inflectional forms, 1,639 of which are lemmatised with this method. A total of 1,149 inflectional forms are classified by type of declension and assigned to 435 lemmas. Most of them are declined according to the as-declension and the a-declension. The main conclusion of this study is that the lemmatisation method comprising linguistic analysis with lexical databases as well as a combination of lexicographical and textual sources of Old English produces solid results. From the methodological point of view, the master lemma list of ParCorOEv2 is adequate for lemmatisation, as lemmas from this list have been assigned to all inflectional forms except 17. On the descriptive side, three new lemmas must be added to the current inventories to lemmatise the nouns beginning with the letter L.